The Effect of Visualized Reading Content on Students’ Reading Motivation - Darmayanti, Ni Putu Era (STKIP AGAMA HINDU SINGARAJA, 2021)
The study was intended to explore the effect of visualized reading content on students’ reading motivation. This study was an experimental study. The present study was an experimental study with pretest-posttest design. This study was conducted in one junior high school in Singaraja and 32 students were involved. The result of analysis found that students reading motivation was better after the implementation of visualized reading content. Thus, it can be said that there is a significant mean difference between students in reading motivation before and after the implementation of visualized reading contents. Teachers are encouraged to implement visualized reading content in order to enhance students’ reading motivation.